Volarea – A Bioinformatics Tool to Calculate the Surface Area and the Volume of Molecular Systems. (25th October 2013) - Ribeiro, João V.; Tamames, Juan A. C.; Cerqueira, Nuno M. F. S. A.; Fernandes, Pedro A.; Ramos, Maria J.
<x xml:space="preserve">Abstract</x> We have developed a computer program named 'VolArea' that allows for a rapid and fully automated analysis of molecular structures. The software calculates the surface area and the volume of molecular structures, as well as the volume of molecular cavities. The surface area facility can be used to calculate the solvent‐exposed surface area of a molecule or the contact area between two molecules. The volume algorithm can be used to predict not only the space occupied by any molecular structure, but also the volume of cavities, such as tunnels or clefts. The software finds wide application in the characterization of systems, such as protein/ligand complexes, enzyme active sites, protein/protein interfaces, enzyme channels, membrane pores, solvent tunnels, among others. Some examples are given to illustrate its potential. VolArea is as a plug‐in of the widely distributed software Visual Molecular Dynamics (VMD) and is freely available at http://www.fc.up.pt/PortoBioComp/Software/Volarea/Home.html.